IS ICT IMPORTANT TO BE INTEGRATED INTO EFL TEACHING: LECTURERS’ POINTS OF VIEW - Yustika Nur Fajriah; Farhan Fauzia (Institut Pendidikan Indonesia Garut, 2019)
Due to the pros and cons of ICT use in the classroom, this study focuses on investigating the lecturers’ perception of the application of ICT-based English teaching in university. To fulfill this aim, this qualitative research through a semistructured interview was conducted to two male EFL lecturers. The data were then analyzed inductively through the phase of recording, transcribing, categorizing, and interpreting. Moreover, the findings show that despite the familiarity with ICT, in the practice, both of them have a different preference; one of the lecturers always use ICT, and the other does not. To conclude, although ICT integration is one of the government’s program in the latest curriculum, the use of ICT is not welcomed by all lecturers.